Cost-effectiveness of broadly neutralizing antibody prophylaxis for HIV-exposed infants in sub-Saharan African settings - (:unkn) unknown (My University, 2023)
Introduction: Infant HIV prophylaxis with broadly neutralizing anti-HIV antibodies (bNAbs) could provide long-acting protection against vertical transmission. We sought to estimate the potential clinical impact and cost-effectiveness of hypothetical bNAb prophylaxis programmes for children known to be HIV exposed at birth in three sub-Saharan African settings. Methods: We conducted a cost-effectiveness analysis using the CEPAC-Pediatric model, simulating cohorts of infants from birth through death in Côte d'Ivoire, South Africa and Zimbabwe. These settings were selected to reflect a broad range of HIV care cascade characteristics, antenatal HIV prevalence and budgetary constraints. We modelled strategies targeting bNAbs to only WHO-designated "high-risk" HIV-exposed infants (HR-HIVE) or to all HIV-exposed infants (HIVE). We compared four prophylaxis approaches within each target population: standard of care oral antiretroviral prophylaxis (SOC), and SOC plus bNAbs at birth (1-dose), at birth and 3 months (2-doses), or every 3 months throughout breastfeeding (Extended). Base-case model inputs included bNAb efficacy (60%/dose), effect duration (3 months/dose) and costs ($60/dose), based on published literature. Outcomes included paediatric HIV incidence and incremental cost-effectiveness ratios (ICERs) calculated from discounted life expectancy and lifetime HIV-related costs. Results: The model projects that bNAbs would reduce absolute infant HIV incidence by 0.3-2.2% (9.6-34.9% relative reduction), varying by country, prophylaxis approach and target population. In all three settings, HR-HIVE-1-dose would be costsaving compared to SOC. Using a 50% GDP per capita ICER threshold, HIVE-Extended would be cost-effective in all three settings with ICERs of $497/YLS in Côte d'Ivoire, $464/YLS in South Africa and $455/YLS in Zimbabwe. In all three settings, bNAb strategies would remain cost-effective at costs up to $200/dose
Keywords: African Research